Sejarah Industri Kerajinan Aluminium Di Desa Menyali,Kecamatan Sawan,Kabupaten Buleleng,Bali Dan Potensinya Sebagai Sumber Belajar Sejarah Di SMA - Ni Made, Putri Oktadewi; Yasa, I Wayan Putra; Pageh, I Made (Widya Winayata : Jurnal Pendidikan Sejarah, 2024)
This research aims to determine: the background, development dynamics and potential of the Menyali Village aluminum craft industry as a source of history learning in high school. The method used in this research is a historical research method which includes: Heuristics, Verification, Interpretation and Historiography. The results of the research show that (1) The background to the emergence of the aluminum craft industry in Menyali Village was influenced by economic factors, raw materials, labor, capital and industrial equipment (2) The aluminum craft industry in Menyali Village experienced development from 1977-2023 seen from the products produced and marketing system (3) The aluminum craft industry can be used as a source of history learning in high school in accordance with the results of curriculum analysis, syllabus as well as cognitive, affective and psychomotor aspects. This research makes a contribution to the field of education, namely as a source for learning history at the high school level and can also be recommended as a P5 topic in the independent curriculum. Keywords: Aluminum, Industry, Crafts, Learning Resources